Ketimpangan dan Prospek Perekonomian di Pulau Sumatera - Yulianita, Anna; Mardhian, Dede; Mukhlis (SAFE-Network, 2023)
Sumatra Island is the third largest island in Indonesia which has extraordinary natural resource potential. Sumatra Island has 10 provinces which are the islands with the most provinces in Indonesia. Each province has different resources and geographical conditions so that inequality occurs with an uneven economy. This study aims to identify leading sectors and prospective sectors in each province in Sumatra. The analysis was carried out on economic inequality between provinces in Sumatra. This study uses the Location Quotient (LQ), Dynamic Location Quotient (DLQ) and Williamson Index (WI) approaches. The results showed that 10 provinces in the Sumatra region had 1 province experiencing high category inequality, 4 provinces experiencing medium category inequality, and 5 provinces experiencing low category inequality. In the LQ analysis it is known that the leading sector for the province in the Sumatra region is the agricultural sector; Forestry and Fisheries; Water Procurement; Waste disposal; Waste Management; Waste and Remediation; and Mining and Quarrying Sector. In the DLQ analysis it is known that each economic sector has prospects for development in the future. The sectors to be developed are Electricity and Gas Procurement; Wholesale and Retail Trade; and Car and Motorcycle Workshop. So that this research can be used as material for consideration and reference for local governments in making policies and synergizing in development in Sumatra.